Spore heat resistance and specific mineralization. - Bender, G R (1985)
Spores of Bacillus megaterium ATCC 19213, Bacillus subtilis niger and Bacillus stearothermophilus ATCC 7953 were converted to fully demineralized, but viable, H forms by controlled acid titration. H forms were more heat sensitive than were native forms, but z values were greater for killing of H spores than those for native spores. Therefore, the differences in heat sensitivity between native and H forms decreased with increasing killing temperature. The increase in heat sensitivity associated with demineralization did not appear to be due to damage to cortex lytic enzymes of the germination system because it could not be moderated by decoating heated H spores and plating them on medium with added lysozyme. H spores could be remineralized by means of back titration with appropriate base solutions. The remineralized spores, except for the Na form, were then more heat resistant than were H spores. Ca and Mn were more effective in restoring resistance than were Mg and K. Generally, the remineralized forms (except for the Na form) had z values greater than those of the native forms but still less than those of the H forms. At lower killing temperatures, the reinstatement of resistance could be related to the extent of remineralization. However, at higher killing temperatures, only a fraction of the mineral was effective in restoring resistance, and higher levels of remineralization did not result in greater resistance. Mineralization is clearly an important factor in spore heat resistance, but the relationship between resistance and mineralization is complex and dependent on killing temperature.